The everyday life of the witnesses of the 2010 earthquake in Chile: rupture, recovery and reconstitution: Rupture, recovery and reconstitution - Vásquez, Juan Saavedra (2022)
This article examines the way in which the 2010 earthquake affected the everyday life of witnesses of this disaster in the southern part of Chile. There were applied 32 in-depth interviews to direct witnesses. There are 3 categories in the path of post-disaster everyday life: rupture, recovery and reconstitution. The results show the witnesses’ quality as biopolitical actors in everyday life in a neoliberal context and the use of biopolitical strategies to produce normality in the frame of this socio-political regime. The shared experience after disaster does not allow to remove the backgrounds in which neoliberal everyday life happens.